Portuguese wine sme competitiveness - financial assessment of Germany entry strategy - Sequeira, Catarina Costa (2021)
Pimentel is a Portuguese Wine SME located in the Douro Valley. I tis present in great potential countries yet capturing only punctual sales from them. As such, Germany was one of the selected countries to provide a thriving entry strategy. To support both this strategy and the marketing recommendations, a financial assessment was performed. By leveraging on the Discounted Cash Flow method, the Net Present Value(NPV) for the five-year project was calculated, providing successful results for the expansion to Germany. The entry strategy proved to be a robust one as several sensitivities generally provided a positive NPV.